Gender Ideologies in Europe: A Multidimensional Framework. Issue 1 (11th January 2018) - Grunow, Daniela; Begall, Katia; Buchler, Sandra
Abstract : The authors argue, in line with recent research, that operationalizing gender ideology as a unidimensional construct ranging from traditional to egalitarian is problematic and propose an alternative framework that takes the multidimensionality of gender ideologies into account. Using latent class analysis, they operationalize their gender ideology framework based on data from the 2008 European Values Study, of which eight European countries reflecting the spectrum of current work–family policies were selected. The authors examine the form in which gender ideologies cluster in the various countries. Five ideology profiles were identified: egalitarian, egalitarian essentialism, intensive parenting, moderate traditional, and traditional. The five ideology profiles were found in all countries, but with pronounced variation in size. Ideologies mixing gender essentialist and egalitarian views appear to have replaced traditional ideologies, even in countries offering some institutional support for gendered separate spheres.